Long-Term [Formula: see text] Exposure and Cause-Specific Mortality in the Latium Region (Italy): A Difference-in-Differences Approach - Renzi, Matteo (Environ Health Perspect, 2019)
BACKGROUND: The link between particulate matter (PM) exposure and adverse health outcomes has been widely evaluated using large cohort studies. However, the possibility of residual confounding and lack of information about the health effects of PM in rural and suburban areas are unsolved issues. OBJECTIVE: Our aim was to estimate the effect of annual [Formula: see text] ([Formula: see text]) exposure on cause-specific mortality in the Latium region (central Italy, of which Rome is the main city) during 2006–2012 using a difference-in-differences approach. METHODS: We estimated daily [Formula: see text] concentrations for each [Formula: see text] of the region from 2006 to 2012 by use of satellite data, land-use predictors, and meteorological parameters. For each of the 378 regional municipalities and each year, we averaged daily [Formula: see text] values to obtain annual mean [Formula: see text] exposures. We applied a variant of the difference-in-differences approach to estimate the association between [Formula: see text] and cause-specific mortality by focusing on within-municipality fluctuations of mortality rates and annual PM exposures around municipality means, therefore controlling by design for confounding from all spatial and temporal potential confounders. Analyses were also stratified by population size of the municipalities to obtain effect estimates in rural and suburban areas of the region. RESULTS: In the period 2006–2012, we observed deaths due to three causes: 347,699 nonaccidental; 92,787 cardiovascular; and 16,509 respiratory causes. The annual average (standard deviation, SD) [Formula: see text] concentration was [Formula: see text] in Latium. For each [Formula: see text] increase in annual [Formula: see text] we estimated increases of 0.8% (95% confidence intervals (CIs): 0.2%, 1.3%), 0.9% (0.0%, 1.8%), and 1.4% ([Formula: see text] , 3.3%) in nonaccidental, cardiovascular, and respiratory mortality, respectively. Similar results were found when we excluded the metropolitan area of Rome from the analysis. Higher effects were estimated in the smaller municipalities, e.g., those with population [Formula: see text] inhabitants. CONCLUSION: Our study suggests a significant association of annual [Formula: see text] exposure with nonaccidental and cardiorespiratory mortality in the Latium region, even outside Rome and in suburban and rural areas. https://doi.org/10.1289/EHP3759